2015
DOI: 10.1007/s13762-015-0883-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of some soil amendments in reducing leaching of fipronil to groundwater

Abstract: The efficacy of different soil amendments in reducing the leaching of fipronil to groundwater was examined in soil columns under laboratory conditions. The polyvinyl chloride columns were sequentially filled with soils of different depths simulating natural conditions. Different soil amendments namely fresh cow dung (FCD) slurry @ 0.5 t ha -1 , farmyard manure @ 5.0 t ha -1 , press mud compost @ 5.0 t ha -1 , cereal straw @ 5.0 t ha -1 and gypsum @ 5.0 t ha -1 were applied on the top soil. The application of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Pesticide quickly dissipates at soil surface within 15 days after treatment and no leaching was observed beyond 30 cm depth. Joshi et al [80] reported that press mud compost and cereal straw were found to be most efficient in decreasing leaching of the fipronil by enhancing its degradation. Pesticides have played a major role in enhancing crop production and crop productivity by controlling diseases and pests.…”
Section: Fipronil Leaching In Soilsmentioning
confidence: 99%
“…Pesticide quickly dissipates at soil surface within 15 days after treatment and no leaching was observed beyond 30 cm depth. Joshi et al [80] reported that press mud compost and cereal straw were found to be most efficient in decreasing leaching of the fipronil by enhancing its degradation. Pesticides have played a major role in enhancing crop production and crop productivity by controlling diseases and pests.…”
Section: Fipronil Leaching In Soilsmentioning
confidence: 99%
“…In recent times spintronic technology has become a focal point for worldwide researchers because it uses both the fundamental degree of freedom of electron and charge [1,2]. It precedes conventional electronic devices because of less power consumption, long-term storage, and high processing speed [3].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, the application of termiticides is the common practice in termite control management. However, excessive and prolonged use of termiticides as the control measure has led to staggering impacts on humans, fishes, livestock and wildlife animals (Floate et al, 2005;Joshi et al, 2016;Petroff 2010;Phung et al, 2012). The adverse effect of overly used termiticides further creates widespread worries among environmentalists.…”
Section: Introductionmentioning
confidence: 99%